2017
DOI: 10.25115/ejrep.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilidad de algunas pruebas estandarizadas para evaluar el funcionamiento de la atención ejecutiva en niños de siete años

Abstract: Introducción. La utilización de pruebas estandarizadas para la evaluación de las habilidades atencionales, es una práctica habitual dentro de contextos clínicos y educativos. Puesto que el concepto de atención resulta algo ambiguo, este estudio intenta examinar la relación entre algunas de estas pruebas y la atención ejecutiva, tal y como es conceptualizada en las aproxi-maciones más recientes de la neurociencia cognitiva. Método. Se administraron algunos subtests del WISC-R, la parte A y B del Trial Making Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To resolve the conflict experienced in the computerized Stroop task (Fuentes et al, 2003), subjects must overcome the powerful tendency to read the word in favor of responding to the color dimension. When subjects must indicate the color of incongruent words (e.g., the word RED in blue letters), difficulty ignoring the intrusive effects of the words results in worse performance (longer reaction time, and/or more errors) than in a neutral condition in which participants indicate the color of meaningless stimuli, in this case a string of colored Xs.…”
Section: Executive Functions Computerized Version Of the Stroop Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…To resolve the conflict experienced in the computerized Stroop task (Fuentes et al, 2003), subjects must overcome the powerful tendency to read the word in favor of responding to the color dimension. When subjects must indicate the color of incongruent words (e.g., the word RED in blue letters), difficulty ignoring the intrusive effects of the words results in worse performance (longer reaction time, and/or more errors) than in a neutral condition in which participants indicate the color of meaningless stimuli, in this case a string of colored Xs.…”
Section: Executive Functions Computerized Version Of the Stroop Taskmentioning
confidence: 99%
“…In order to measure inhibitory control in deaf and hearing groups, two computerized tasks were used: a computerized version of the Stroop task (Fuentes et al, 2003) and a short version of the Child-ANT (Rueda et al, 2004). The Stroop task used in the present study has been shown to be adequate to obtain a Stroop interference effect in 7-year-old hearing children (Fuentes et al, 2003), since it only requires that children have automated reading of three color words ("RED, " "GREEN, " and "BLUE"). The Child-ANT does not use verbal information, only visual information, and the version used in the present study has been shown to be adequate in deaf children from age 6 (Daza and Phillips-Silver, 2013).…”
Section: Introductionmentioning
confidence: 99%